Only when <em>b</em> = 0 or <em>k</em> = 1<em>.</em>
If <em>f(x)</em> = <em>mx</em> + <em>b</em>, then
<em>f</em> (<em>kx</em>) = <em>m</em> (<em>kx</em>) + <em>b</em> = <em>mkx</em> + <em>b</em>
while
<em>k</em> <em>f(x)</em> = <em>k</em> (<em>mx</em> + <em>b</em>) = <em>kmx</em> + <em>kb</em>
The two expression are identical only if
<em>kb</em> = <em>b</em> ===> <em>kb</em> - <em>b</em> = 0 ===> <em>b</em> (<em>k</em> - 1) = 0 ===> <em>b</em> = 0 or <em>k</em> = 1
Answer:
the equation that determines the length of the base, sorry i forgot the name of it
Step-by-step explanation:
1. Replace f(x) with y: y = 3x - 15
2. Interchange x and y: x = 3y - 15
3. Solve this for y: 3y = x + 15, and y = (x + 15)/3
4. Replace y with
-1 -1
f (x): f (x) = (x + 15) / 3 (answer)
The answer is 7 times 4 goes into 30.
<u>Step-by-step explanation</u>:
- To check how many times a number goes into a larger number, use division.
- Divide 30 by 4.
⇒ 4
7 = 28 and 30-28 = 2
⇒ The quotient is 7.
⇒ The remainder is 2.
So, the number 4 goes 7 times into 30.